Sustained censorship in BH (2026-03) (Bahrain) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Bahrain. Data sourced from OONI.
Censorship Incident ID: BH-2026-0105. Severity: critical. Confidence: 75%